A novel LC-MS method development and validation for the determination of phenyl vinyl sulfone in eletriptan hydrobromide - Indhu Priya Mabbu; G. Sumathi; N. Devanna (SpringerOpen, 2021)
Abstract Background The aim of the present method is to develop and validate a specific, sensitive, precise, and accurate liquid chromatography-mass spectrometry (LC-MS) method for the estimation of the phenyl vinyl sulfone in the eletriptan hydrobromide. The effective separation of the phenyl vinyl sulfone was achieved by the Symmetry C18 (50 × 4.6 mm, 3.5 μm) column and a mobile phase composition of 0.1%v/v ammonia buffer to methanol (5:95 v/v), using 0.45 ml/min flow rate and 20 μl of injection volume, with methanol used as diluent. The phenyl vinyl sulfone was monitored on atomic pressure chemical ionization mode mass spectrometer with positive polarity mode. Results The retention time of phenyl vinyl sulfone was found at 2.13 min. The limit of detection (LOD) and limit of quantification (LOQ) were observed at 1.43 ppm and 4.77 ppm concentration respectively; the linear range was found in the concentration ranges from 4.77 to 27.00 ppm with regression coefficient of 0.9990 and accuracy in the range of 97.50-102.10%. The percentage relative standard deviation (% RSD) for six replicates said to be injections were less than 10%. Conclusion The proposed method was validated successfully as per ICH guidelines. Hence, this is employed for the determination of phenyl vinyl sulfone in the eletriptan hydrobromide.